2021
DOI: 10.3390/cli9060090
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Perceptions by Smallholder Coffee Farmers in the Northern and Southern Highlands of Tanzania

Abstract: Smallholder farmers are among the most vulnerable groups to climate change. Efforts to enhance farmers’ adaptation to climate change are hindered by lack of information on how they are experiencing and responding to climate change. Therefore, this paper examines smallholder farmers’ perceptions of climate change, factors influencing their perceptions, and the impacts and adaptation strategies adopted over the past three to four decades. A list of farmers was obtained from the Agricultural Marketing Cooperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
3
14
0
2
Order By: Relevance
“…Farmers perceive different climate events and the events are usually interrelated. Available literature in sub-Saharan Africa has largely treated the determinants of perception singly see [16,[33][34][35][36][37][38] without due consideration to the interrelated nature of perceived climate events. Although we are aware of the study of Liverpool-Tasie et al [12], an exception in Nigeria, that considered the interrelated nature of farmers perceived climate events, the study however dealt with maize and poultry farmers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Farmers perceive different climate events and the events are usually interrelated. Available literature in sub-Saharan Africa has largely treated the determinants of perception singly see [16,[33][34][35][36][37][38] without due consideration to the interrelated nature of perceived climate events. Although we are aware of the study of Liverpool-Tasie et al [12], an exception in Nigeria, that considered the interrelated nature of farmers perceived climate events, the study however dealt with maize and poultry farmers.…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variables are the perceived climate events and they are listed below: The choice of the independent variables was supported by available literature on factors influencing climate change perception in sub-Saharan Africa [12,16,[33][34][35][36][37][38]. We used the STATA software to carry out the multivariate probit regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, different studies indicate that smallholder coffee farmers have been responding to climate change impacts through a range of interventions, including agronomic practices such as planting shade trees, pruning, planting drought-tolerant varieties, and application of organic fertilizers (Kajembe et al, 2016;Wagner et al, 2018;Mbwambo et al, 2021). In the study by Pham et al (2019), adaptation and management practices were identified by more than 70% of total studies (25 papers), of which agro forestry, either through intercropping or shading, was most common (18 papers), followed by irrigation and efficient use and management of water (12 papers), development of new cultivars that are drought and heat-stress resistant and/or pest and disease tolerant (10 papers) and diversification of cropping patterns or livelihood activities (9 papers).…”
Section: Introductionmentioning
confidence: 99%